Behavioral phenotype and sleep problems in SATB2‐associated syndrome. (16th August 2019) - Cotton, Allison Pierce; Gokarakonda, Srinivasa; Caffrey, Aisling R; Zarate, Yuri A; Kumar, Nihit
Abstract : Aim: To determine the nature and frequency of behavioral phenotypes and sleep disturbances in individuals with SATB2 ‐associated syndrome (SAS). Method: The Strengths and Difficulties Questionnaire (SDQ) and an age‐appropriate sleep questionnaire were distributed to the parents of individuals with SAS. All scores were compared to available normative data. Results: Thirty‐one individuals completed the assessment (18 females, 13 males; mean age 7y 4mo [SD 4y 1mo], range 2–16y). Individuals with SAS had significantly higher Total Difficulty scores than the normative sample (14.9 [SD 5.8] vs 7.1 [SD 5.7], p <0.001). A high frequency of emotional problems (22.6% vs 8%, p= 0.01), peer problems (48.4% vs 10%, p <0.001), hyperactivity (48.4% vs 9%, p <0.001), and low prosocial behaviors (45.2% vs 9%, p <0.001) contribute to the behavioral profile in SAS. Concurrent sleeping difficulties were also frequently identified. Ten individuals in the 5 to 15 years age range had at least one sleep disorder (mean Sleep Disturbance Scale for Children total score 40.9 [SD 8.4] vs 35.1 [SD 7.7], p <0.001). Interpretation: With previous limited available objective neurobehavioral data on the SAS population, we reported evidence of high‐risk for a broad spectrum of burdensome behavioral phenotype and concurrent sleeping difficulties, the latter being particularly prevalent during early childhood. Routine assessment and treatment for behavioral issues and sleep problems is recommended. What this paper adds: Emotional and peer problems, hyperactivity, and low prosocial behavior are common in SATB2 ‐associated syndrome. The Strength and Difficulties Questionnaire Total Difficulty scores are atypical in nearly half of individuals. Behavioral difficulties are perceived as burdensome to over half of the parents. Nearly half of individuals have at least one sleep disorder. Sleep–wake transition disorders were most common. What this paper adds: Emotional and peer problems, hyperactivity, and low prosocial behavior are common in SATB2 ‐associated syndrome. The Strength and Difficulties Questionnaire Total Difficulty scores are atypical in nearly half of individuals. Behavioral difficulties are perceived as burdensome to over half of the parents. Nearly half of individuals have at least one sleep disorder. Sleep–wake transition disorders were most common.